Submersion with grommets: contamination is possible at minimal depth, as demonstrated with a novel middle-ear model. Issue 7 (7th July 2022) - Farrell, E; Gendre, A; Viani, L; Glynn, F; Walshe, P
Abstract: Objective: Advice to patients following grommet insertion and waterproofing can vary from clinician to clinician. A laboratory based experiment was performed to determine at what depth water contamination would occur through various grommet tubes. Methods: A novel experimental ear model was developed using an artificial tympanic membrane and ventilation tubes. Water contamination was identified using an effervescent solid that reacts when in contact with water. Measures of dispersion were used to describe the results. Results: The average depth of water contamination was: 19.64 mm (range = 11–33 mm, standard deviation = 5.55 mm) using a Shepard grommet; 20.84 mm (range = 18–26 mm, standard deviation = 1.97 mm) with a titanium grommet; and 21.36 mm (range = 18–33 mm, standard deviation = 3.03 mm) using a T-tube. Water contamination was possible at depths of 11–33 mm. The average pressure at water effervescent activation was 0.20 kPa. Conclusion: Submersion underwater at any depth with grommets is likely to lead to middle-ear contamination. These findings are concordant with clinical studies.